Prerequisites of Formation the Paradigm of Financial Provision for Business Entities Sustainable Development - Lidiia Kostyrko; Liudmyla Zaitseva (Облік і фінанси, 2020)
Globalization trends in the world economy lead to changes in the economic conditions of enterprises activity and the distribution of financial resources to ensure their sustainable development. Sustainable development of enterprises largely depends on the state of their financial support and the choice of financing instruments. Therefore, the priority task is to study the financial nature of capital transformations under the influence of economic processes and revise approaches to the formation of a paradigm for financial support for business entities sustainable development. The purpose of the article is to substantiate the prerequisites of the paradigm of financial support for business entities sustainable development and directions of its implementation. The steady recovery of capital is required to ensure the sustainable development of business entities. Therefore, businesses should apply different modern instruments of raising financial resources: self-financing, bank lending, budget financing and crediting, redistribution of funds, and placement of financial instruments. The article presents the process of optimizing the ratio of forms and volumes of financial resources of economic activity, aimed at improving the efficiency of financing sustainable development of business entities. Based on a systematic analysis of the use of the set of concepts, the indicators of financial support for sustainable development of business entities have been determined. The results of the critical analysis of the fundamental theoretical bases of sustainable development and their development with the help of new postulates have allowed to develop the initial theoretical provisions of the paradigm of financial support for sustainable development. The main idea of this paradigm is to formulate adequate financial support for maximizing the value of a sustainable development-oriented company. It was proved that the value of the company reflects a complex system of economic relations and is the effective indicator of the potential for sustainable development.